Lignin beyond the status quo : recent and emerging composite applications - Fazeli, Mahyar; Mukherjee, Sritama; Baniasadi, Hossein; Abidnejad, Roozbeh; Mujtaba, Muhammad; Lipponen, Juha; Seppälä, Jukka; Rojas, Orlando J (Green chemistry : an international journal and green chemistry resource : GC, 2024)
The demand for biodegradable materials across various industries has recently surged due to environmental concerns and the need for the adoption of renewable materials. In this context, lignin has emerged as a promising alternative, garnering significant attention as a biogenic resource that endows functional properties. This is primarily ascribed to its remarkable origin and structure that explains lignin's capacity to bind other molecules, reinforce composites, act as an antioxidant, and endow antimicrobial effects. This review summarizes recent advances in lignin-based composites, with particular emphasis on innovative methods for modifying lignin into micro and nanostructures and evaluating their functional contribution. Indeed, lignin-based composites can be tailored to have superior physicomechanical characteristics, biodegradability, and surface properties, thereby making them suitable for applications beyond the typical, for instance, in ecofriendly adhesives and advanced barrier technologies. Herein, we provide a comprehensive overview of the latest progress in the field of lignin utilization in emerging composite materials.